Development of Species-Specific PCR Primers for the Rapid and Simultaneous Identification of the Six Species of Genus Takifugu - Dong, Chun Mae (Dev Reprod, 2019)
Pufferfish (Takifugu spp.) are economically important edible marine fish. Mistakes in pufferfish classification can lead to poisoning; therefore, accurate species identification is critical. In this study, we used the mtDNA cytochrome c oxidase subunit I gene (COI) to design specific primers for six Takifugu species among the 21 domestic or imported pufferfish species legally sold for consumption in Korea. We rapidly and simultaneously identified these pufferfish species using a highly efficient, multiplex polymerase chain reaction (PCR) system with the six species-specific primers. The results showed that species-specific multiplex PCR (multiplex species-specific polymerase chain reaction; MSS-PCR) either specifically amplified PCR products of a unique size or failed. MSS-PCR yielded amplification fragment lengths of 897 bp for Takifugu pardalis, 822 bp for T. porphyreus, 667 bp for T. niphobles, 454 bp for T. poecilonotus, 366 bp for T. rubripes, and 230 bp for T. xanthpterus using the species-specific primers and a control primer (ca. 1,200 bp). We visualized the results using agarose gel electrophoresis to obtain accurate contrasts of the six Takifugu species. MSS-PCR analysis is easily performed and provides identification results within 6 h. This technique is a powerful tool for the discrimination of Takifugu species and will help prevent falsified labeling, protect consumer rights, and reduce the risk of pufferfish poisoning..